Understanding potentials and restrictions of solvent-free enzymatic polycondensation of itaconic acid: an experimental and computational analysis - Corici, Livia; Pellis, Alessandro; FERRARIO, VALERIO; EBERT, CYNTHIA; CANTONE, SARA; GARDOSSI, Lucia (Advanced Synthesis & Catalysis, 2015)
Itaconic acid is a chemically versatile unsaturated diacid that can be produced by fermentation and potentially it can replace petrol based monomers such as maleic and fumaric acids in the production of curable polyesters or new biocompatible functionalized materials. Unfortunately, due to the presence of the unsaturated C=C bond, polycondensation of itaconic acid is hampered by cross reactivity and isomerization. Therefore, enzymatic polycondensations would respond to the need of mild and selective synthetic routes for the production of novel bio-based polymers. The present work analyses the feasibility of enzymatic polycondensation of diethyl itaconate and, for the first time, provides comprehensive solutions embracing both the formulation of the biocatalyst, the reaction conditions and the choice of the co-monomers. Computational docking was used to disclose the structural factors responsible for the low reactivity of dimethyl itaconate and to identify possible solutions. Surprisingly, experimental and computational analysis revealed that 1,4-butanediol is an unsuitable co-monomer for the polycondensation of dimethyl itaconate whereas the cyclic and rigid 1,4-cyclohexanedimethanol promotes the elongation of the oligomers.